Language and socialization? It is all about sociosemiotics - Salmani Nodoushan, Mohammad Ali (Rivista Italiana di Filosofia del Linguaggio, 2022)
Language socialization is an interdisciplinary area of linguistic inquiry that addresses the question of how the processes of socialization and language acquisition lead to and benefit from each other. It comprises both a theoretical perspective on the processes of socialization and language acquisition and a methodological approach to the study of human development in socio-cultural milieus. Its comparative research agenda is an amalgamation of longitudinal research, microanalysis, and ethnography, and it is founded on the assumptions (1) that socio-culturally defined contexts are prerequisite to human learning, and (2) that human language has the capacity to index implicit and explicit meanings present in character or emergent from content and context. This paper provides an overview of language socialization and expatiates upon its potential to predict the future of human societies. The pars destruens, à la Bacon (1620), of this paper aims at removing all errors and misunderstandings that exist in connection to language socialization, and its pars construens aims at presenting a true picture of the topic from the perspective of sociosemiotics. The landslide aftermaths of language socialization for human societies in general, and totalitarian and/or theocratic societies in specific, are discussed.